Degradation of benzoic acid in an advanced oxidation process: The effects of reducing agents - He, Dong-Qin; Zhang, Ying-Jie; Pei, Dan-Ni; Huang, Gui-Xiang; Liu, Chang; Li, Jun; Yu, Han-Qing (Journal of hazardous materials, 2020)
[Display omitted] •Dosing reducing agents resulted in enhanced pollutant degradation and expansion of pH range.•Dosing manner of RA was a key factor governing its roles in Fenton system.•Catalytic mechanisms of the three reducing agents in Fenton system were proposed.•Electrical energy per order was used to estimate the costs of three reducing agents. Fenton reaction is widely used for hazardous pollutant degradation. Reducing agents (RAs) have been proven to be efficient in promoting the generation of HO• in Fenton reaction by accelerating the redox cycle of Fe3+/Fe2+. However, the roles of different RAs in Fenton reaction remain unrevealed. In this work, the catalytic activity of three RAs, i.e., hydroxylamine (NH2OH), ascorbic acid (AA) and cysteine (Cys), on the degradation of benzoic acid (BA) and the hydroxyl radical formation in the Fenton-RAs system were investigated. Results show the catalytic performance of RAs in BA degradation by Fenton reaction followed an order of NH2OH > AA > Cys. Compared with the conventional Fenton system, the effective pH range in the Fenton-NH2OH system extended from 3.0 to 5.0, while the optimal pH in the Fenton-AA and Fenton-Cys systems ranged from 3.0 to 4.0. The Fenton-AA system exhibited a two-stage reaction toward BA degradation, which was different from the Fenton-NH2OH and Fenton-Cys systems. Furthermore, the dosing manner of AA was found to be a key factor governing its role in the Fenton-AA system. This observation suggests the different mechanisms behind the enhancement of the three RAs in Fenton system. Different from NH2OH and Cys, AA would inhibit the generation of HO•, especially at the fast stage of degradation process, where Fe3+ has not accumulated yet. In addition, the economic analysis using the electrical energy per order indicates Fenton-NH2OH system was economically feasible with the lowest energy input, compared to Fenton-AA and Fenton-Cys systems. These results are useful to better understand the roles of RAs in Fenton system, and also provide guidance about the selection and dosing manner of suitable RAs in the advanced oxidation processes.